2007
DOI: 10.1007/s12072-007-9024-3
|View full text |Cite
|
Sign up to set email alerts
|

Immune selection during chronic hepadnavirus infection

Abstract: Purpose Late-stage outcomes of chronic hepatitis B virus (HBV) infection, including fibrosis, cirrhosis, and hepatocellular carcinoma (HCC) result from persistent liver injury mediated by HBV antigen specific cytotoxic T lymphocytes (CTLs). Two other outcomes that often accompany chronic infection, the emergence of mutant viruses, including HBe-antigen negative (HBeAg (-)) HBV, and a reduction over time in the fraction of hepatocytes productively infected with HBV, may also result from persistent immune attack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 58 publications
3
36
0
Order By: Relevance
“…Previous investigations showed that HBV DNA in the host cell genome can produce enough surface antigen molecules for HDV virion assembly even in the absence of precore and pregenomic RNAs and regardless of an active HBV replication [32,33] . These cells, which still produce some of the viral products, may be selected through immune responses, appear as a result of a resolved infection or just due to the support of the infected cells for parts of the viral proteins such as envelope antigens but not the complete replication of the virus [33][34][35] . Nonetheless, regarding the role of HBV as an envelope provider, HDV nucleoproteins can be considered as competitors with HBV for HBsAg.…”
Section: Replicationmentioning
confidence: 99%
“…Previous investigations showed that HBV DNA in the host cell genome can produce enough surface antigen molecules for HDV virion assembly even in the absence of precore and pregenomic RNAs and regardless of an active HBV replication [32,33] . These cells, which still produce some of the viral products, may be selected through immune responses, appear as a result of a resolved infection or just due to the support of the infected cells for parts of the viral proteins such as envelope antigens but not the complete replication of the virus [33][34][35] . Nonetheless, regarding the role of HBV as an envelope provider, HDV nucleoproteins can be considered as competitors with HBV for HBsAg.…”
Section: Replicationmentioning
confidence: 99%
“…Thus, a number of HDV-infected hepatocytes apparently may not display markers of HBV replication. In addition, HDV is able to suppress HBV replication (2,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The observations presented above indicate that HDV and HBV, while being present in the same liver, may not necessarily be present in the same cell.…”
mentioning
confidence: 95%
“…Normal hepatocytes that are apparently free of HBV replication markers but still express HBV envelope proteins can appear as a result of resolved HBV infection or via immunemediated selection. In addition, HCC cells may apparently no longer support HBV replication but can still support the production of envelope proteins from HBV integrants (3,(14)(15)(16)(25)(26)(27) (28)(29)(30)(31)(32)(33). In addition, the functional properties of integrant-derived HBV surface antigens (HBsAgs) remain to be fully evaluated (16, 29-31, 34, 35).…”
mentioning
confidence: 99%
“…Some of the virus-free hepatocytes form foci of altered hepatocytes (FAH) with morphology similar to that of liver cancer cells and are considered premalignant. In addition, the cells of hepadnavirus-induced HCCs often were reported to be virus free as well (1,4,(15)(16)(17)(18)(19)(20)(21)(22)(23). In contrast, several previous studies reported the presence of hepadnaviral , making the issue still controversial.…”
mentioning
confidence: 99%